(untitled) (Vietnam Journal of Community Medicine, 2024)
Aims of review: Describe the paraclinical symptoms of workers with pneumoconiosis treated at the Central Lung Hospital in 2022-2023. Research method: A descriptive study with purposive sampling was conducted at the Department of Occupational Lung Diseases, Central Lung Hospital on all 60 patients with pneumoconiosis who met the selection criteria. Results and conclusion: Generally, subclinical symptoms can be observed on chest X-ray results according to ILO 2011 standards and lung ventilation function testing. Chest X-ray: lung parenchymal lesions are mainly small opacities with size p (20.0%), the main subgroup is small opacities with density 1 (45%); 26.7% of patients had large opacities (type A large opacities accounted for the highest proportion with 15.0%; type B accounted for 10.0% and type C was rarer with 1.7%). Exploration of ventilatory function: mainly encountered patients with limited erectile dysfunction (23.3%), obstructive erectile dysfunction (33.3%), and mixed erectile dysfunction (1.7%). Of these, 20% have mildly limited neuropathy; 16.67% of patients had moderate obstructive erectile dysfunction; Patients with mixed erectile dysfunction account for only 1.67%. It is necessary to diagnose pneumoconiosis early and carry out lifelong monitoring and management of pneumoconiosis according to the instructions of the health sector.